Ultrafast Nonlinear Optical Response and Carrier Dynamics in Layered Gallium Sulfide (GaS) Single-Crystalline Thin Films - Lu, Haishuang; Chen, Yu; Yang, Kexin; Kuang, Yawei; Li, Zhongguo; Liu, Yushen (Frontiers in Materials, 2021)
Gallium sulfide (GaS) is a layered metal monochalcogenide semiconductor that has recently garnered considerable attention in various fields. In this study, we investigated the nonlinear absorption characteristics of multilayer β-GaS thin films on sapphire substrate by using femtosecond open-aperture Z-scan method. The β-GaS films exhibit saturable absorption behavior at 532 nm while nonlinear absorption appears under 650 nm excitation. The nonlinear absorption coefficient of β-GaS was determined to be -1.8 × 10-8 m/W and 4.9 × 10-8 m/W at 532 and 650 nm, respectively. The carrier dynamics of β-GaS films was studied via femtosecond transient absorption (TA) measurements. The TA results demonstrated that β-GaS films have broad photo-induced absorption in the visible regime and sub-nanosecond lifetime. Our results indicate that gallium sulfide has large nonlinear optical response and long carrier lifetime, which could be applied in future photonic devices.